Emerging Concern with Imminent Therapeutic Strategies for Treating Resistance in Biofilm - Ramendra Pati Pandey; Riya Mukherjee; Chung-Ming Chang (MDPI AG, 2022)
Biofilm production by bacteria is presumed to be a survival strategy in natural environments. The production of biofilms is known to be influenced by a number of factors. This paper has precisely elaborated on the different factors that directly influence the formation of biofilm. Biofilm has serious consequences for human health, and a variety of infections linked to biofilm have emerged, rapidly increasing the statistics of antimicrobial resistance, which is a global threat. Additionally, to combat resistance in biofilm, various approaches have been developed. Surface modifications, physical removal, and the use of nanoparticles are the recent advances that have enabled drug discovery for treating various biofilm-associated infections. Progress in nanoparticle production has led to the development of a variety of biofilm-fighting strategies. We focus on the present and future therapeutic options that target the critical structural and functional characteristics of microbial biofilms, as well as drug tolerance mechanisms, such as the extracellular matrix, in this review.